Cytokines as effectors and predictors of responses in the treatment of bladder cancer by bacillus Calmette–Guérin. (June 2014) - Liu, Xiaoxuan; Dowell, Alexander C; Patel, Prashant; Viney, Richard P; Foster, Michael C; Porfiri, Emilio; James, Nicholas D; Bryan, Richard T
ABSTRACT: : The most effective intravesical treatment of non-muscle-invasive bladder cancer is instillation of live Mycobacterium bovis bacillus Calmette–Guérin (BCG). BCG stimulates the release of cytokines, contributing directly or indirectly to its effectiveness. However, the function of specific cytokines is not well understood. We have undertaken a nonsystematic review of primary evidence regarding cytokine detection, activation and response in BCG patients. Cytokines IL-2, IL-8 and TNF-α appear to be essential for effective BCG therapy and nonrecurrence, while IL-10 may have an inhibitory effect on BCG responses. IL-2, IL-8, TRAIL and TNF-α are potentially predictive of response to BCG. Alterations in genes encoding cytokines may also affect responses. There are significant data showing the association of certain cytokines with successful BCG treatment, and which may be useful predictive markers. Isolating those cytokines mediating efficacy may hold the key to ameliorating BCG's side effects and improving efficacy and patient compliance.